Exploration of the mechanical behavior of metal organic frameworks UiO-66(Zr) and MIL-125(Ti) and their NH2 functionalized versions. Issue 10 (24th November 2015) - Yot, Pascal. G.; Yang, Ke; Ragon, Florence; Dmitriev, Vladimir; Devic, Thomas; Horcajada, Patricia; Serre, Christian; Maurin, Guillaume
Abstract : The structural behaviour under mechanical stimuli of two metal organic frameworks, UiO-66(Zr) and MIL-125(Ti) and their amino-functionalized derivatives has been investigated by high-pressure powder X-ray diffraction up to 3.5 GPa. Abstract : The structural behaviour under mechanical stimuli of two metal organic frameworks, UiO-66(Zr) and MIL-125(Ti) and their amino-functionalized derivatives has been investigated by high-pressure powder X-ray diffraction up to 3.5 GPa. All these solids showed a gradual pressure-induced reversible decrease of their crystallinity and UiO-66(Zr)_NH2 material has been revealed as one of the most resilient MOFs reported so far corresponding to a very high bulk modulus. The mechanical behaviors of these MOFs have been correlated to their chemical and geometric features including the metal–oxygen coordination number, the nature of the organic linker, the porosity as well as their crystal density.